Spectral amplitude coding OCDMA using and subtraction technique - Hasoon, Feras N.; Syed Alwee Aljunid, Syed Junid; Samad, M.D.A.; Mohamad Khazani, Abdullah; Sahbudin, Shaari (Optical Society of America, 2009)
Link to publisher's homepage at http://www.opticsinfobase.org